(untitled) (Research, Society and Development, 2020)
Objective: to perform the cross-cultural adaptation and practicality test for the use of the Critical Care instrument, Pressure Ulcer Assessment Tool Made Easy, in Brazil. Methods: methodological study of cross-cultural adaptation, including five stages: initial translation, synthesis of the initial translation, back-translation, evaluation by a committee of experts and the performance of the feasibility test, applied to the assessment of the risk of pressure injuries in patients in intensive care. Results: The content validity index (CVI) was calculated for analysis by the expert committee and the agreement rate (TC) for practicality in the pre-test. From this, CVI> 0.8 and TC> 80% were considered favorable and the semantic and idiomatic equivalences were considered adequate, with CVI of 0.85 and TC of 84.38%. Final considerations: the scale was adapted for use in Brazil, showed a high level of agreement among specialists during all stages and demonstrated content validity.